The beginnings of vernacular scientific discourse: genres and linguistic features in some early issues of the Journal des Sçavans and the Philosophical Transactions - David BANKS (E-REA)
The Journal des Sçavans and the Philosophical Transactions were both founded in 1665. The Journal des Sçavans was founded by Denis de Sallo and was mainly intended as a journal of book reviews, conceived of as a way of disseminating new knowledge. It covered the whole range of human knowledge. The Philosophical Transactions was founded by Henry Oldenberg, with a mandate, but without funding, from the Royal Society. It was based on the numerous letters that he received, and restricted itself to matters of “natural philosophy”. This article looks in detail at some of the linguistic features of one issue of the Journal des Sçavans (9 March 1665), and one issue of the Philosophical Transactions (3 July 1665). An analysis of transitivity patterns shows that relational process and verbal process constitute the most common types in the Journal des Sçavans, whereas in the Philosophical Transactions, although the rate of relational process is similar, the rate for material process is four times higher. An analysis of thematic structure shows that the Philosophical Transactions has rather less textual themes than the Journal des Sçavans. In terms of thematic progression, the Philosophical Transactions has slightly less linear links and rather more constant links than the Journal des Sçavans. A semantic categorization of themes shows that the most common categories in the Journal des Sçavans relate to the author of the book being reviewed, or to the book itself, whereas in the Philosophical Transactions the commonest category by far is the object of study.